Relationship between corporate culture and psychological safety of training and educational space for young female athletes - Kalenchuk , Valentyna Oleksandrivna; Fedchuk , Oleksandr Valeriyovych; Mykhaylyuk , Vitalii Pavlovich (Insight: the psychological dimensions of society, 2023)
The purpose is to establish correlations between the ideas of young female athletes about corporate culture and psychological safety of training and educational space. The empirical research involved young female athletes (aged 15-17 years; M=16.12; SD=3.11), who trained and studied at a higher school of physical culture (Group I) (n=28; 60.87%) and representatives of this school who continued their sporting and educational-professional career at a higher educational institution (aged 18-21 years; M=19.56; SD=4.05), at the faculties of physical culture and sport and the faculty of psychology, history and sociology (Group II) (n=18; 39.13%). The sample consisted of young athletes who went in for such sports as: handball, volleyball and field and track. Methods: we applied valid methods tested in the sporting area of methodology which allowed determining three types of corporate culture and psychological content parameters of safety of training and educational space. The empirical data are presented through descriptive frequency characteristics. Statistical reliability coefficients – α-Cronbach, Spearman’s correlation (rs), Students’s t-test were used. Results. Different structures of the types of corporate culture of sports educational institutions were created and significant differences of a closed type (CT) (t=-2.42; р
Keywords: safe space, young students, psychology of achievement, adolescence, sport for adolescents